2014
DOI: 10.1111/jre.12180
|View full text |Cite
|
Sign up to set email alerts
|

Do subjects with aggressive and chronic periodontitis exhibit a different cytokine/chemokine profile in the gingival crevicular fluid? A systematic review

Abstract: The current weight of evidence is not sufficient to prove that there are distinct gingival crevicular fluid cytokine/chemokine profiles for patients with aggressive periodontitis and chronic periodontitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
44
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(45 citation statements)
references
References 35 publications
1
44
0
Order By: Relevance
“…27,29,54 It is known that the quality of the host immuneinflammatory response against bacterial challenge determines the severity and extent of disease. 56,57 CP and G-AgP are different disease entities with different etiology and pathogenesis. 58 Although the initiation of the disease may differ a similar immunopathogenesis in both diseases have been suggested.…”
Section: Discussionmentioning
confidence: 99%
“…27,29,54 It is known that the quality of the host immuneinflammatory response against bacterial challenge determines the severity and extent of disease. 56,57 CP and G-AgP are different disease entities with different etiology and pathogenesis. 58 Although the initiation of the disease may differ a similar immunopathogenesis in both diseases have been suggested.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is important to highlight that other recent studies have questioned a real difference between the chronic and aggressive forms of periodontitis (Van der Velden, ). A recent systematic review examined the profile of cytokines in the gingival crevicular fluid and concluded that the current weight of evidence is not sufficient to prove a difference between AP and CP (Duarte et al, ). Moreover, a microbiological study on bacterial screening of Aggregatibacter actinomycetemcomitans and Porphyromonas gingivalis in individuals with CP or AP concluded that the detection of these known periodontopathogenic bacterias is not able to discriminate different forms of periodontitis (Nibali et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…No adverse effect was observed. 39 For the present study, MMP-1 and MMP-9 were chosen as two inflammatory mediators actively involved in the connective tissue remodelling process. 21 The cost-effectiveness of such structured plaque control intervention was previously reported.…”
Section: Manual Brush (N = 16)mentioning
confidence: 99%